2016
DOI: 10.2525/ecb.54.17
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polyamines in Plant Disease Resistance

Abstract: Polyamines (PAs) are small, aliphatic amines that are found in all living cells. In plants, putrescine, spermidine, spermine, and thermospermine are known as ubiquitous PAs. They are involved in various physiological processes and environmental stress responses, including pathogen infections. Several studies have demonstrated that PAs and their catabolic products, such as H2O2 produced by diamine oxidases and polyamine oxidases, are closely involved in the activation of host defense mechanisms. This minireview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…Polyamines are present in all life forms and are involved in a plethora of cellular processes including growth, development, stress response, and pathogenesis (reviewed in Valdes-Santiago et al, 2012; Minocha et al, 2014; Miller-Fleming et al, 2015; Takahashi, 2016; Pal and Janda, 2017). Consequently, the PA metabolic pathway in the host plant as well as in the pathogen has been the target of a number of studies to improve disease resistance in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines are present in all life forms and are involved in a plethora of cellular processes including growth, development, stress response, and pathogenesis (reviewed in Valdes-Santiago et al, 2012; Minocha et al, 2014; Miller-Fleming et al, 2015; Takahashi, 2016; Pal and Janda, 2017). Consequently, the PA metabolic pathway in the host plant as well as in the pathogen has been the target of a number of studies to improve disease resistance in plants.…”
Section: Discussionmentioning
confidence: 99%
“…As Orn is synthesized from Glu, which serves both as an entry point for N, and a major precursor for several other AAs in plants, alterations in PA metabolism can impact AA levels in living cells (Mohapatra et al, 2010; Majumdar et al, 2013, 2016). The role of PAs in plant disease resistance is highly evident from several studies that involved alteration of tissue PA concentrations through genetic manipulations or exogenous application of PAs (reviewed in Jiménez-Bremont et al, 2014; Takahashi, 2016; Pal and Janda, 2017). Over-expression of a human SAMDC gene in tobacco resulted in increased accumulation of free and conjugated PAs and conferred tolerance to Verticillium dahliae and Fusarium oxysporum (Waie and Rajam, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are common to both plants and fungal pathogens, and their metabolism can play significant roles in host defense as well as successful pathogenesis and mycotoxin production during compatible host-pathogen interactions ( Gardiner et al, 2009 , 2010 ; Valdés-Santiago and Ruiz-Herrera, 2013 ; reviewed in Takahashi, 2016 ). It was demonstrated that the fungus Tapesia yallundae , rendered avirulent due to inactivation of the odc gene, had virulence restored upon re-introduction back into plants, possibly due to the uptake of PAs from the host thus compensating for PA depletion in the pathogen ( Mueller et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, along with the increased vegetative growth and earlier flowering in the transgenic lines, ectopic expression of GhSAMDC 1 increased total polyamines and spermine, and reduced spermidine. Expression analysis of NtSPDS [1][2][3][4][5] and NtSPMS demonstrated that NtSPDS 4 and NtSPMS were downregulated and upregulated, respectively, in the transgenic lines ( Fig. 1), indicating that the conversion of spermidine to spermine might be regulated by NtSPDS 4 and NtSPMS in tobacco.…”
Section: Discussionmentioning
confidence: 99%